2021
DOI: 10.1016/j.trsl.2020.12.007
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in patients with systemic lupus erythematosus: lessons learned from the inflammatory disease

Abstract: As the world navigates the Coronavirus disease 2019 (COVID-19) pandemic, there is a growing need to assess its impact in patients with autoimmune rheumatic diseases, such as systemic lupus erythematosus (SLE). Patients with SLE are a unique population when considering the risk of contracting COVID-19 and infection outcomes. The use of systemic glucocorticoids and immunosuppressants, and underlying organ damage from SLE are potential susceptibility factors. Most patients with SLE have evidence of high type I IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 258 publications
(398 reference statements)
1
76
0
5
Order By: Relevance
“…We particularly emphasise the scarcity of robust information regarding treatment in immunosuppressed patients with COVID-19. ► We present a case of a patient with deteriorating COVID- 19 under the effect of RTX, who experienced a rapid and notable improvement after IVIg treatment. Despite lacking strong evidence, IVIg might be a promising therapeutic choice in RTX-treated patients and its use considered in this population.…”
Section: Learning Pointsmentioning
confidence: 99%
“…We particularly emphasise the scarcity of robust information regarding treatment in immunosuppressed patients with COVID-19. ► We present a case of a patient with deteriorating COVID- 19 under the effect of RTX, who experienced a rapid and notable improvement after IVIg treatment. Despite lacking strong evidence, IVIg might be a promising therapeutic choice in RTX-treated patients and its use considered in this population.…”
Section: Learning Pointsmentioning
confidence: 99%
“…Moreover, the treatment of SLE includes immunosuppressants and corticosteroids that could increase patients’ vulnerability to infections. On the other hand, recent studies have shown that immunosuppressive therapies seem to reduce systemic inflammation and the risk of developing respiratory distress syndrome in COVID-19 patients [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Male sex, older age, obesity, arterial hypertension, and atherosclerotic disease, well-known conditions predisposing to endothelial dysfunction, are significantly related to cardiac and vascular complication during COVID-19 disease 3 , 6 . Furthermore, COVID-19 infection likely induces or exacerbates autoimmune disease in predisposed patients, although in absence of definitive data [7] , [8] , [9] , [10] , [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Some earlier studies aimed to investigate if SARS-CoV-2 infection modulates SLE disease prevalence, however they have not found a substantial vulnerability of COVID-19 in infected SLE patients [48,49]. A small cohort study by Fernandez-Ruiz et al reported that COVID-19 confirmed SLE patients have a higher hospitalization rate compared to the general population, independent of mortality rate [50]. The immunosuppressive treatment in SLE patients has not shown a higher rate of SARS-CoV-2 infection or COVID-19 symptoms [51].…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%